The effect and timing of local anesthesia in laparoscopic cholecystectomy - YEGEN, ŞEVKET CUMHUR (LIPPINCOTT WILLIAMS & WILKINS, 1996)
Although postoperative pain following laparoscopic cholecystectomy (LC) is less intense than that after open surgery, postoperative morbidity nonetheless increases with LC. The aim of this study was to investigate whether local anesthetic infiltration of trocar sites during LC decreased postoperative pain and, if so, to find the optimum timing for local anesthesia (LA). Seventy patients undergoing LC were randomized into three groups. In the first (control group, n = 25) 3 ml of 0.9% NaCl was subcutaneously infiltrated around each 5-mm trocar site, 4 ml around each 10-mm site. In the second group (n = 20), the same volume of local anesthetic was administered in the same manner prior to surgery, and in the third group (n = 25) an identical dose of local anesthetic was infiltrated al the end of surgery. A visual analog scale was given to all patients, who were asked to record their pain intensity at 1, 3, 5, 7, and 12 h postoperatively. Pethidine HCl I mg/kg i.m. was given to those whose pain intensities were greater than 5. The mean pain intensities were 7.6, 5.9, and 5.1 in the control, preoperative, and postoperative LA groups, respectively, In the preoperative LA group, 50% of patients and in the postoperative LA group 28% of patients required analgesics compared with 76% in the control group. The main pain intensities and analgesic requirements were significantly lower in the postoperative LA group compared with other groups. We conclude that local anesthesia during LC reduces postoperative pain and that infiltration of trocar sites following surgery offers better pain relief than local anesthetic given just before the incision.
Keywords: laparoscopic cholecystectomy; local anesthesia; POSTOPERATIVE PAIN RELIEF; PREEMPTIVE ANALGESIA; WOUND INFILTRATION; BUPIVACAINE; HERNIORRHAPHY